2016
DOI: 10.1177/0973801016645216
|View full text |Cite
|
Sign up to set email alerts
|

The Feldstein–Horioka Puzzle and Structural Breaks: Evidence from the Largest Countries of Asia

Abstract: The purpose of this paper is to investigate the level of capital mobility in the largest economies of Asia by testing the Feldstein-Horioka puzzle. Panel estimations using quarterly data for the period from 1995 to 2011 have been made for the seven largest economies of Asia, specifically Russia, Japan, South Korea, Turkey, India, Indonesia and China. This group of countries has gained significant economic power in the world over the last decade.Specifically, the growth rates of the sample has for a long period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Khundrakpam and Ranjan (2010) found a weaker relationship between saving and investment rates with the inclusion of the post-reform period which depicts the era of more liberalised capital flows. Ketenci (2016) found lower saving retention coefficient and thus, higher international capital mobility in the post-Asian crisis period. In another study, Phiri (2017) found increase in international capital mobility in the post-global financial crisis period thereby weakening the F–H high correlation between domestic savings and investment.…”
Section: Literature Reviewmentioning
confidence: 91%
See 1 more Smart Citation
“…Khundrakpam and Ranjan (2010) found a weaker relationship between saving and investment rates with the inclusion of the post-reform period which depicts the era of more liberalised capital flows. Ketenci (2016) found lower saving retention coefficient and thus, higher international capital mobility in the post-Asian crisis period. In another study, Phiri (2017) found increase in international capital mobility in the post-global financial crisis period thereby weakening the F–H high correlation between domestic savings and investment.…”
Section: Literature Reviewmentioning
confidence: 91%
“…This, on the one hand, implies the presence of a tendency for international capital mobility, and on the other hand, indicates fiscal deficit induced deteriorating current account balance (CAB) position in South Asian economies. Given the argument that countries with relatively higher capital mobility are more likely to be exposed to the adverse effects of international market fluctuations (Ketenci, 2016), the novelty of this study is the inclusion of the global financial recession shock (2007)(2008)(2009) in explaining F-H puzzle in the post-liberalisation era. The remaining of the study is organised as follows: Section II reviews the relevant literature to justify the research problem and set the building block of the study; Section III presents observations from the trends in domestic savings and investment in the SAARC region; Section IV elaborates the data and methodology used in the study; Section V draws inferences from the empirical analyses; Section VI makes the concluding remark; and Section VII notes down the scope for further study while pointing out the limitations.…”
Section: Introductionmentioning
confidence: 99%
“…They found the cointegrating relationships between national saving and investment and also found a higher degree of relationship between capital mobility and trade openness for Asian nations. Ketenci (2016) revisited the FH puzzle for seven selected largest economies of Asia using quarterly data from 1995 to 2011. The empirical results found evidence of moderate capital mobility in stable countries (Japan, South Korea, and India) and relatively higher capital mobility in unstable countries (Russia, Turkey, Indonesia, and China).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of these studies have focused on Asian countries (Abdul Latif et al, 2015;Adebola and Dahalan, 2012;Ang, 2007;Kaur and Sarin, 2019;Ketenci, 2016;Khundrakpam and Ranjan, 2010;Narayan, 2005;Yildirim and Orman, 2018). While some of them have confirmed a high international capital mobility (Ketenci, 2016;Yildirim and Orman, 2018), others have found that there is a low capital mobility (Abdul Latif et al, 2015;Adebola and Dahalan, 2012;Ang, 2007;Narayan, 2005;Kaur and Sarin, 2019;Kkhundrakpam and Ranjan, 2010;Yildirim and Orman, 2018). In some other studies, it has been found that there is low capital mobility for developing countries (Grullon, 2016;Phiri, 2019;Tursoy and Faisal, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%